Tuberculosis and Leprosy Coinfection: A Perspective on Diagnosis and Treatment. (5th June 2018) - Mangum, Lisa; Kilpatrick, Dustin; Stryjewska, Barbara; Sampath, Rahul
Abstract: Both leprosy and tuberculosis (TB) are known to have similar geographic endemicity. In the setting of coinfection, interferon-gamma release assays (IGRAs) to detect latent TB can be falsely positive. We report a case of leprosy with a positive IGRA and asymptomatic active pulmonary TB. Minocycline and dapsone therapy was initiated during the workup for TB and changed to rifampin (Rif), isoniazid, pyrazinamide, and ethambutol, with the addition of dapsone once coinfection was confirmed. Our review of the literature revealed a preponderance of coinfection reported with borderline and lepromatous disease. Ten patients were diagnosed with leprosy as the first infection; 7 of these patients (70%) were treated with Rif before TB diagnosis, and 70% (7/10) of coinfected patients were on steroids. If treatment for leprosy is a consideration before ruling out active TB, then minocycline may temporarily replace the Rif. The dire implications of Rif monotherapy in undiagnosed coinfection may warrant chest radiography with or without sputum microbiology as routine initial workup for all leprosy cases.